El acto administrativo: La arbitrariedad producida desde y a partir del acto administrativo - Romero-Pérez, Jorge Enrique (2014)
The administrative act is a key element in the understanding of the modern State. Being this a micro aspect, it allows comprehending the macro dimension macro of Public Administration. The presumption that the administrative act is according to law, with its enforceability effects (such as the capacity of Public Administration to enforce the administrative act by its own means), and application (being this understood as the obligation of making such activity demandable) implies the criticism that it is a mere presumption that illegal actions and de facto (not de jure) actions are an everyday reality.